Pengaruh Strategi Pembelajaran dan Kemampuan Berpikir Ilmiah terhadap Hasil Belajar Kimia - Andri Wahyu Wijayadi (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2017)
Solubility and solubility product topic consists of abstract concepts and mathematic calculation. Mastering of concepts in this topic requires Scientific Reasoning Skills (SRS). Teaching of solubility and solubility product topic expected to developing students’ SRS. Therefore, students’ learning outcomes tends to be high. The purposes of this research are to find out the difference of learning outcomes of students learned using guided inquiry and verification strategies regarding students’ SRS. This research applied a 2 x 2 factorialized design. Data were score of SRS and learning outcomes analyzed using Two Ways ANOVA statistics. The results showed that learned using guided inquiry strategy and higher level of SRS gave higher learning outcomes.